Participation in Activities and Autonomy with an Impact toward Task Performance and Contextual Performance among Engineers - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan; Razak, Azley Abd (Canadian Center of Science and Education, 2019)
This study explores the relationship and the impact of the participation in related activities and autonomy of job performance toward task performance and contextual performance of job performance. The study was conducted on the electrical and electronics (E&E) engineers in the Bayan Lepas Free Trade Zone, Penang. Self-administered questionnaires were distributed through the E&E manufacturing companies’ human resource managers. A total of 1,100 questionnaires were distributed that adapted and adopted the research tools of Govino on participation in related activities, Conway and Monks on autonomy, Williams and Anderson on task performance, and Hochwarter et al. on contextual performance. A total of 181 were returned but 150 questionnaires were useable for this study. A factor analysis was conducted on all variables of the study. Interestingly, participation in work-related variables had been divided into participation in HR-related activities and participation in work-related activities. Results indicated that participation in HR-related activities had no association with task performance but had a low relationship with the contextual performance. Furthermore, the participation in work-related activities had no relationship with both, the task performance and the contextual performance. Finally, the engineers indicated that their autonomy had a low relationship with the task performance and moderate relationship with the contextual performance